Identifying the effect of vancomycin on health care–associated methicillin-resistant Staphylococcus aureus strains using bacteriological and physiological media. Issue 1 (9th January 2021) - Rajput, Akanksha; Poudel, Saugat; Tsunemoto, Hannah; Meehan, Michael; Szubin, Richard; Olson, Connor A; Seif, Yara; Lamsa, Anne; Dillon, Nicholas; Vrbanac, Alison; Sugie, Joseph; Dahesh, Samira; et al.
Abstract: Background: The evolving antibiotic-resistant behavior of health care–associated methicillin-resistant Staphylococcus aureus (HA-MRSA) USA100 strains are of major concern. They are resistant to a broad class of antibiotics such as macrolides, aminoglycosides, fluoroquinolones, and many more. Findings: The selection of appropriate antibiotic susceptibility examination media is very important. Thus, we use bacteriological (cation-adjusted Mueller-Hinton broth) as well as physiological (R10LB) media to determine the effect of vancomycin on USA100 strains. The study includes the profiling behavior of HA-MRSA USA100 D592 and D712 strains in the presence of vancomycin through various high-throughput assays. The US100 D592 and D712 strains were characterized at sub-inhibitory concentrations through growth curves, RNA sequencing, bacterial cytological profiling, and exo-metabolomics high throughput experiments. Conclusions: The study reveals the vancomycin resistance behavior of HA-MRSA USA100 strains in dual media conditions using wide-ranging experiments.